Reestructuración Técnico Administrativa en la empresa Ferresolda, en la Ciudad de Bogotá, D.C. (2018)
The restructuring technical and management in the Ferresolda Company in the Bogota D.C city, has some problems identified in the development of the project. The purpose of this problems were giving some advice for the solutions to this problems. In the project will analyze external and internal factors of the company. The diagnostic which is the first chapter was developed some analyses and opportunities of the subsector through the Porters forces and the camara de comercio de Bogotá diagnostic. The technical study gave as result some improvements in the description of the services that the company offer, the times study gave as result a improvement in the plant distribution. The management study allows make a functions manual, also the organization chart was organized and a salary study.